Isozyme polymorphisms within Pyrenophora tritici-repentis population in Argentina - Moreno, Maria Virginia (2008)
Tan spot caused by Pyrenophora tritici-repentis is an economically important disease of wheat (Triticum aestivum L.) in Argentina. The success of local breeding programs for resistance to the disease depends to a large extent on the genetic variation within the pathogen population. To assay this variability, 155 isolates of P. tritici-repentis obtained from leaves of wheat and Festuca sp. of different localities were assayed and compared for isozyme polymorphisms. Isozyme analysis was performed with polyacrilamide gel electrophoresis in the systems estearase, phosphatase and peroxidase. Variation in the number and relative mobility of the bands by each system was detected in this collection of isolates. Intraspecific polymorphisms were identified in the three systems assayed. The cluster analysis based in bands patterns defined 86 electromorph types among the 155 isolates evaluated according with the Jaccard’s coefficient (CCC = 095). The isozymes patterns were not correlated with the geographic and/or wheat cultivars origin of the P. tritici-repentis isolates.